IMPLEMENTASI E-MODUL BERBASIS KEARIFAN LOKAL DENGAN PENDEKATAN MODEL CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN MOTIVASI SISWA DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Desi Ratna Sari; Nursiwi Nugraheni; Nanik Wijayanti; Decky Avrilianda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools is often still conventional and less connected to students' cultural backgrounds, resulting in low motivation and suboptimal learning outcomes. This study aims to analyze the implementation of local wisdom-based e-modules using the Culturally Responsive Teaching (CRT) approach to improve students' learning motivation and learning outcomes in elementary schools. The research employed a Systematic Literature Review (SLR) method by reviewing various national and international scientific journal articles published between 2020 and 2025. The review process was conducted through stages of identification, screening, eligibility, and inclusion based on the PRISMA procedure. The findings indicate that the implementation of local wisdom-based e-modules integrated with the CRT approach positively affects students' motivation and learning outcomes. The integration of local culture into learning materials, the use of interactive multimedia, contextual learning experiences, digital assessment, and teacher guidance were found to increase students' engagement, conceptual understanding, critical thinking skills, digital literacy, and active participation in learning. In addition, the CRT approach creates a more inclusive, meaningful, and enjoyable learning environment because students' cultural identities are recognized and valued in the learning process. Therefore, local wisdom-based e-modules with the CRT approach can serve as an innovative learning alternative to support contextual and culturally responsive learning in elementary schools.